Molecular surveillance of potential SARS-CoV-2 reservoir hosts in wildlife rehabilitation centers. Issue 1 (31st December 2023) - Mena, Juan; Hidalgo, Christian; Estay-Olea, Daniela; Sallaberry-Pincheira, Nicole; Bacigalupo, Antonella; Rubio, André V.; Peñaloza, Diego; Sánchez, Carolina; Gómez-Adaros, Javiera; Olmos, Valeria; Cabello, Javier; Ivelic, Kendra; et al.
Abstract: Background: The COVID-19 pandemic, caused by SARS-CoV-2 infection, has become the most devastating zoonotic event in recent times, with negative impacts on both human and animal welfare as well as on the global economy. Although SARS-CoV-2 is considered a human virus, it likely emerged from animals, and it can infect both domestic and wild animals. This constitutes a risk for human and animal health including wildlife with evidence of SARS-CoV-2 horizontal transmission back and forth between humans and wild animals. Aim: Molecular surveillance in different wildlife rehabilitation centers and wildlife associated institutions in Chile, which are critical points of animal-human interaction and wildlife conservation, especially since the aim of wildlife rehabilitation centers is to reintroduce animals to their original habitat. Materials and Methods: The survey was conducted in six WRCs and three wildlife associated institutions. A total of 185 samples were obtained from 83 individuals belonging to 15 different species, including vulnerable and endangered species. Each specimen was sampled with two different swabs: one oropharyngeal or nasopharyngeal according to the nostril diameter, and/or a second rectal sample. RNA was extracted from the samples and two different molecular assays were performed: first, a conventional RT-PCR with pan-coronavirus primers and a second SARS-CoV-2 qPCR targeting the N and S genes. Results: All 185 samples were negative for SARS-CoV-2. Clinical relevance: This study constitutes the first report on the surveillance of SARS-CoV-2 from wildlife treated in rehabilitation centers in Chile, and supports the biosafety procedures adopted in those centers.